PENGEMBANGAN FLIPBOOK BERBASIS DIGITAL UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN FIKIH MATERI QURBAN KELAS V MI DARUL HIKAM KOTA BATU - khoiriyah, rosa nur (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Fakultas Ilmu Tarbiyah dan Keguruan UIN Maulana Malik Ibrahim Malang, 2025)
At elementary school level, fiqh is studied with the aim of ensuring that students are able to practice the provisions of Islamic law properly and correctly as a form of obedience to Islamic teachings, both as a relationship between themselves and Allah SWT, with other people and with the environment. One of the materials taught to students is sacrificial material. Evidence that students have met the learning outcomes is by looking at the students' learning outcomes. Good learning outcomes indicate that learning outcomes have been met, and vice versa. This research uses Research and Development (R&D) research with the ASSURE model. The development steps in this model include: (1) analyze student (conduct an analysis of the student's character), (2) state objects (set goals in learning) (3) select method. media and materials (choosing media and learning methods as well as teaching materials), (4) utilize materials (utilize teaching materials), (5) requile learnest participation (involve students in learning), (6) evaluate and revise (evaluate and revise learning programs ). The results of this research and development are digital-based flipbook learning media products for class V Fiqh subject matter